2009
DOI: 10.2337/db08-1074
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Stearoyl-CoA Desaturase (SCD)-1 Activity and Diacylglycerol but Not Ceramide Concentrations Are Increased in the Nonalcoholic Human Fatty Liver

Abstract: OBJECTIVE-To determine whether 1) hepatic ceramide and diacylglycerol concentrations, 2) SCD1 activity, and 3) hepatic lipogenic index are increased in the human nonalcoholic fatty liver.RESEARCH DESIGN AND METHODS-We studied 16 subjects with (n ϭ 8) and without (n ϭ 8) histologically determined nonalcoholic fatty liver (NAFL ϩ and NAFL Ϫ ) matched for age, sex, and BMI. Hepatic concentrations of lipids and fatty acids were quantitated using ultra-performance liquid chromatography coupled to mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
139
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(163 citation statements)
references
References 64 publications
(60 reference statements)
22
139
1
1
Order By: Relevance
“…Similar data were observed when liver fat was plotted against the splanchnic production rate of TAGs (47). TAGs containing saturated or monounsaturated fatty acids also predominate in liver biopsy samples of subjects with increased compared with normal liver fat content (49). Consistent with these data, the absolute serum concentrations of the abundant TAGs containing monounsaturated and saturated fatty acids were significantly increased in the obese group compared with the 'nonobese' group (Supplementary Table 2).…”
Section: The Pnpla3supporting
confidence: 78%
“…Similar data were observed when liver fat was plotted against the splanchnic production rate of TAGs (47). TAGs containing saturated or monounsaturated fatty acids also predominate in liver biopsy samples of subjects with increased compared with normal liver fat content (49). Consistent with these data, the absolute serum concentrations of the abundant TAGs containing monounsaturated and saturated fatty acids were significantly increased in the obese group compared with the 'nonobese' group (Supplementary Table 2).…”
Section: The Pnpla3supporting
confidence: 78%
“…Because the TG fraction contained significantly less stearate and polyunsaturated fatty acids (C20:3N6, C20:4N6, C22:6N3) and more oleate than the PL fraction, the indices of elongase, DNL, and SCD1 activity show strong differences between the hepatic lipid fractions. Such differences may have a major influence if total, unfractionated fatty acids are analyzed in tissue samples with different TG content (34 ). An increase in the triglyceride fraction would lead to a positive correlation between TG content and the desaturase and DNL indices as well as a negative correlation between TG content and elongase index and polyunsaturated fatty acid content solely due to the increasing proportion of TG-derived fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic gene expression of sterol regulatory element-binding protein (SREBP) 1c, key transcriptional activator of lipogenic genes, as well as of acetyl-CoA carboxylases (ACCs) and fatty acid synthase (FAS) have been shown to be increased in subjects with as compared to those without NAFLD [43]. Analyses of fatty acid composition revealed that the there is an excess of saturated fatty acids and saturated fatty acids -containing triglycerides in the human fatty liver [44]. In addition, the activity of a lipogenic enzyme stearoyl-CoA desaturase 1 (SCD1) is increased and the percentage of long polyunsaturated fatty acids decreased in subjects with as compared to those without NAFLD [44].…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…Analyses of fatty acid composition revealed that the there is an excess of saturated fatty acids and saturated fatty acids -containing triglycerides in the human fatty liver [44]. In addition, the activity of a lipogenic enzyme stearoyl-CoA desaturase 1 (SCD1) is increased and the percentage of long polyunsaturated fatty acids decreased in subjects with as compared to those without NAFLD [44]. This could decrease the ability of long polyunsaturated fatty acids to inhibit SREBP-1c activity [45] and [46].…”
Section: De Novo Lipogenesismentioning
confidence: 99%
See 1 more Smart Citation